2021
DOI: 10.1002/bmc.5064
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity and nephrotoxicity assessment on ethanol extract of Fructus Psoraleae in Sprague Dawley rats using a UPLC–Q‐TOF–MS analysis of serum metabolomics

Abstract: Fructus Psoraleae (FP) is commonly used in the treatment of vitiligo, osteoporosis, and other diseases in clinic. As a result, the toxicity caused by FP is frequently encountered in clinical practice; however, the underlying toxicity mechanism remains unclear. The purpose of this study was to investigate the toxic effect of the ethanol extract of FP (EEFP) in rats and to explore the underlying toxic mechanisms using a metabolomics approach. The toxicity was evaluated by hematological indicators, biochemical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The nephrotoxicity of 70% ethanol extracts of PCL (0.54, 1.08, and 1.62 g/kg) in rats was examined using UPLC-Q-TOF–MS serum metabolomics. It was discovered that the 70% ethanol extracts of PCL could interfere with phospholipid metabolism, amino acid metabolism, purine metabolism, and antioxidant system activity, leading to nephrotoxicity [ 161 ]. The furanocoumarins of PCL (20, 40 mg/kg) could interfere the metabolism, excretion and bioavailability of endogenous and exogenous compounds to damage kidney functions by affecting renal organic ion transport system [ 162 ].…”
Section: Nephrotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The nephrotoxicity of 70% ethanol extracts of PCL (0.54, 1.08, and 1.62 g/kg) in rats was examined using UPLC-Q-TOF–MS serum metabolomics. It was discovered that the 70% ethanol extracts of PCL could interfere with phospholipid metabolism, amino acid metabolism, purine metabolism, and antioxidant system activity, leading to nephrotoxicity [ 161 ]. The furanocoumarins of PCL (20, 40 mg/kg) could interfere the metabolism, excretion and bioavailability of endogenous and exogenous compounds to damage kidney functions by affecting renal organic ion transport system [ 162 ].…”
Section: Nephrotoxicitymentioning
confidence: 99%
“…Over 163 chemicals have so far been identified from fresh PCL. A number of phytochemical studies have revealed that PCL primarily contains coumarins , flavonoids , monoterpene phenols , benzofurans (140)(141)(142)(143)(144)(145)(146)(147)(148)(149) and other compounds (150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163). Among them, coumarins, flavonoids and monoterpene phenols are considered to be the PCL's primary bioactive components.…”
Section: Phytochemistrymentioning
confidence: 99%
“…In the present study, we applied the mice liver and serum metabolomics in vivo combined with in vitro (HepG2 cells) to explore the underlying mechanisms for the hepatoxicity induced by AFM1 and OTA. The metabolomics of individual liver or serum has been used to characterize toxicological outcomes induced by various hazard factors, such as ethanol and silica nanoparticles [37][38][39]. However, the combined metabolomics of liver and serum is relatively insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…PF is a widely used Chinese medicine, containing bioactive components such as coumarin, benzofuran, flavonoids, and monoterpenes [ 12 ]. Due to clinical application, it has been found that PF has a toxic effect on the liver [ 9 ], and animal studies have shown that PF has hepatotoxicity and nephrotoxicity to normal rats [ 19 , 20 ]. Traditional Chinese medicine processing technology is an effective means to reduce the toxicity of traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%